TRANSMISI ILMU DALAM PENDIDIKAN SUFISTIK - Humaisi, M. Syafiq (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2012)
Abstract: Transmission of knowledge through Wasilah in Sufi education paradigm has led students to be human beings who have impeccable character. Sufi education seeks to integrate the common mind, the heart and the actualization of the common mind and heart in man towards the purification of the soul. There are at least three stages taught by educators in building studentsâ character, the first stage, the seeker (al-murid) is a person who has sets of awareness and belief as a creature of God as creator. The second is musafir (al-sair), a servant of the upright walk with God. The last stage is al-wasil, a servant who attains perfect knowledge of God. The education that is now unfolding should refer to the objectives and philosophy of Sufi essential educational goals. The foundation listed in the Law on National Education System (UUSPN) should not only be an ideal setting and the plain theory, but also come in the realm of actualization and realization that can shape the character of each individual learner. Meaningful education that contains educational value should be the priority in the learning process. This can be done by activating the three basic domains in education such as cognitive, affective and psychomotor.